Public Speaking and Career Advancement: Experiences of Past Student Leaders from Ghana Institute of Journalism - Essandoh, Mavis; Aboagye Da-Costa, Caroline (Cradle of Knowledge: African Journal of Educational and Social Science Research (The), 2024)
Public speaking is a relevant skill, especially for those who aspire to be leaders, including student leaders. Being able to communicate effectively, eloquently, making meaningful statements as well as persuading people to agree to your opinion cannot be taken for granted for anyone who aspires to take a public leadership position. Similar to any democratic political system, winning leadership position in institutions of higher learning requires persuasive skills to make colleagues buy into your vision to win. Though some people have the natural ability to speak eloquently and communicate their thoughts publicly, others learn to do that, fostering the incorporation of public speaking into the curricular for Public Relations students at the Ghana Institute of Journalism (GIJ). Using the Theory of Communicative Action and a qualitative methodology, this study sought to understand how student leaders in GIJ came by their public speaking skills and how it impacted their career choices. Findings indicate that students who took up leadership positions had mastered the public speaking skills through social institutions before entering GIJ, partly because they had the leadership aspiration. The curriculum training was seen as a supplement to harness that skill, and the art of public speaking greatly influenced their career choices.
Research Article
Keywords: Public Speaking, Career Advancement, Student Leaders, Ghana Institute of Journalism, Ghana